Pengabdian Kepada Masyarakat Pemeriksaan Kesehatan (Hipertensi, Kolesterol Tinggi, Asam Urat, Gula Darah) Di Lingkungan Pendidikan Al-Aitaam Kabupaten Bandung - Upus Piatun Khodijah; Irma Rosliani Dewi; Ajeng Windyastuti Ardini; Neng Rika Rismayanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
One form of attention from universities to the social and cultural environment of the community (Tri Dharma Perguruan Tinggi) is through community service activities. With the establishment of a harmonious relationship between Higher Education and the community, it is hoped that it can provide input for improving the quality of Higher Education needed by the community. On November 12, 2022, a Community Service Activity was carried out in the form of a Health Check including checking blood pressure, cholesterol levels, blood sugar levels and uric acid levels, in the Sali Al-Aitaam environment. Health checks were carried out on 173 people in the Sali Al-Aitaam neighborhood. From the results of the examination, there were 102 people (58.9%) with high blood pressure, 67 people (38.7%) with high blood sugar levels, 72 people (41.6%) with high uric acid levels, and 91 people (52.6%) with high cholesterol levels. Hypertension, High Cholesterol, Uric Acid, Blood Sugar diseases from the results of the examinations carried out show that many people still experience these diseases and the cause is because people are less concerned and do not want to do health checks to health workers or independently. Health workers need to provide education to the community in the Sali Al-Aitaam neighborhood about health checks to determine and control blood pressure, blood sugar, cholesterol and uric acid so as to prevent possible diseases that will arise such as hypertension, diabetes and so on.